Application of project-based learning method in Entrepreneurship education (PKWU) subjects of Labschool UPI - Dzakira Syawalia; Amanda Febrilyanti Suryana Putri; Razka Raditya Fahmi; Dimas Saputra (Universitas Pendidikan Indonesia, 2024)
This study reviews the application of project-based learning methods in PKWU subjects of SMA Labshool UPI. The subject of Entrepreneurship Education (PKWU) has an important role in preparing students for the world of work and entrepreneurship. In this context, the purpose of the study is to identify the potential and effectiveness of project-based learning methods in improving students' understanding and skills in PPKWU subjects at the senior secondary level. This research also aims to design, implement, and evaluate the implementation of project-based learning methods that can integrate theory with practice in the classroom. This study used qualitative research methods using interview instruments to explore student experiences in the application of Project Based Learning Methods in PKWU subjects at SMA Labschool UPI. The results of this study show that the application of project-based methods in learning Crafts and Entrepreneurship subjects has a positive and significant impact on student development. One key aspect that stands out is the increased involvement of students in learning.